Linguagem verbal e não verbal no ensino de biologia - Peres, Janaina Campos (2020)
The learning process is dialogic, inside it there is the need to communicate harmoniously. There is no communication without language, therefore,education needs language. There are many ways of language, based on the sound, on the visual ando n the verbal mode. The educator must use all didactic resource to students learning development, unfourtunately, it does not often happen in our schools. Must of the classes are based on the verballanguage (written and oral), the exclusivity of this language form or its excessive repetition mecanizes the classes, the level of student’s interest decreases, the dialogue processes fails and with it the communication. In this scenarion students do not learnand sometimes they just get the information by heart. This istudy aims to demonstrate that is possible the usage of many diferent languages, mainly the non verbal ones, to teach Biology to first year Senior High School students at a Technical Highschool in São Paulo. The dissertation is divided in three chapters where the first brings a technical research about the language conccept, origin and function, regarding it to cultural and biological aspects. As it deals with language, the second chapter was driven to the semiotic thought. The Peirce’s cathegories were connected to didactic materials and with the languageused in them. In the last chapter is presented the projects developed with students. The data collection was made by a questionary which aimed to demonstrate the students’ level of knowledge and level of proximity with the didactic resourses. Through the answers, it aimed to plan classes in which other ways of language could be used, mainly non verbal ones.Two class plans were made and used througout the school year. The teacher role at school, his preparation and the way he runs those activities is pivotal to this study. The teacher needs to be as plural as the languages are and also to be creative. The educator must be engaged and up to the changes, inovations, and chalanges the nowadays education im poses us.